2023
DOI: 10.3389/fimmu.2023.1104124
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibodies to Omicron after the fourth SARS-CoV-2 mRNA vaccine dose in immunocompromised patients highlight the need of additional boosters

Abstract: IntroductionImmunocompromised patients have been shown to have an impaired immune response to COVID-19 vaccines.MethodsHere we compared the B-cell, T-cell and neutralizing antibody response to WT and Omicron BA.2 SARS-CoV-2 virus after the fourth dose of mRNA COVID-19 vaccines in patients with hematological malignancies (HM, n=71), solid tumors (ST, n=39) and immune-rheumatological (IR, n=25) diseases. The humoral and T-cell responses to SARS-CoV-2 vaccination were analyzed by quantifying the anti-RBD antibodi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Due to the significant waning of antibody levels in the months following the third dose [ 39 , 46 ] and the emergence of SARS-CoV-2 variants with a high potential of immune escape, the European Center for Disease Prevention and Control and European Medicine Agency recommended, in July 2022, the administration of the fourth dose to people above 60 years of age as well as to vulnerable persons of any age [ 47 ]. The fourth vaccine dose has been shown to elicit higher antibody levels than the third dose in immunocompromised patients [ 48 ] but lower levels than in the controls in studies with patients on immunosuppressive therapy [ 49 ] and RD [ 50 ]. Few studies have, however, reported NAbs, T cell-mediated or hybrid immunity, and the persistence of antibodies after the fourth dose in patients with CKD and RD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the significant waning of antibody levels in the months following the third dose [ 39 , 46 ] and the emergence of SARS-CoV-2 variants with a high potential of immune escape, the European Center for Disease Prevention and Control and European Medicine Agency recommended, in July 2022, the administration of the fourth dose to people above 60 years of age as well as to vulnerable persons of any age [ 47 ]. The fourth vaccine dose has been shown to elicit higher antibody levels than the third dose in immunocompromised patients [ 48 ] but lower levels than in the controls in studies with patients on immunosuppressive therapy [ 49 ] and RD [ 50 ]. Few studies have, however, reported NAbs, T cell-mediated or hybrid immunity, and the persistence of antibodies after the fourth dose in patients with CKD and RD.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported increased neutralizing activity and T-cell response after the fourth dose in patients with RD. However, in only a minority of the subjects, the level of neutralization against the Omicron BA.2 strain was above baseline [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have, however, reported NAbs, T cell mediated or hybrid immunity and persistence of antibodies after fourth dose in patients with CKD and RD. One study reported increased neutralizing activity and T cell response after fourth dose in patients with RD, with only a minority displaying a level of neutralization above baseline for the Omicron BA.2 strain [49].…”
Section: Discussionmentioning
confidence: 99%
“…Due to significant waning of antibody levels in the months following the third dose [38, 44, 45] and the emergence of SARS-CoV-2 variants with a high potential of immune escape The European Center for Disease Prevention and Control and European Medicine Agency recommended in July 2022 the administration of the fourth dose to people above 60 years as well as vulnerable persons of any age [46]. Fourth vaccine dose has been shown to elicit higher antibody levels than after the third dose in immunocompromised patients [47], but lower levels than in controls after three doses in studies with patients on immunosuppressive therapy [48], RD [49] and with CKD [40, 44]. Few studies have, however, reported NAbs, T cell mediated or hybrid immunity and persistence of antibodies after fourth dose in patients with CKD and RD.…”
Section: Discussionmentioning
confidence: 99%